Rampart Roads in the Peat Lands of Ireland: Genesis, Development and Current Performance - O'Kelly, Brendan (My University, 2008)
The construction and improvement of roads on peat lands has always been a challenging task in geotechnical engineering. Rampart roads, which are a particular feature of the bog roads in Ireland, are caused by the excavation of peat from the roadsides over many years for use as a domestic fuel. The historical development of rampart roads and current performance under the added traffic loading is discussed. Various road improvement methods have been applied to improve the road ability to carry traffic and the technical aspects and performance of the methods are discussed. In particular, the performance of the improvement methods is related to the geotechnical properties of the underlying bog foundation.
Invited presentation at the First International Conference on Transportation Geotechnics
PUBLISHED
Nottingham, UK
Keywords: Peat